Optimalisasi Sumber Daya untuk Hidup Sehat dan Berdaya - Wening Asih Sutrisno; Mamay Maulana; Muhamad Reza Pahlevi; Tri Nur Jayanti; Hairani Hairani (Warta Pengabdian Andalas, 2023)
Health problems are not only indicated by disease. Attention also needs to be given to people who are between healthy and sick with promotive and preventive efforts. The activity was carried out by optimizing existing resources through promotive and preventive efforts to increase community independence in health status. This community service activity was conducted in Sukabakti Village from 8 August to 21 September 2023. It included health screening, hypertension exercises, optimizing the Harum Madu program by planting medicinal and vegetable seeds, and health education about hypertension. Counselling was also given to students at SDN 2 Sukabakti about Clean and Healthy Living Behavior and students at SMP Plus Al-Kohar and Vocational School Insan Prima Mandiri about reproductive health. The results of the health examination screening showed that several participants had blood pressure >140/90 mmHg and blood sugar >140 mg/dL, they did hypertension exercises well, optimized the Harum Madu program by planting chilli and shallot seeds, and students had a better understanding of the counselling topics provided. It is hoped that the information presented during this activity can be applied to achieve optimal health.